Interchromosomal recombination is suppressed in mammalian somatic cells. - Shulman, M J (1995)
Homologous recombination occurs intrachromosomally as well as interchromosomally, both in mitotic (somatic) cells as well as meiotically in the germline. These different processes can serve very different purposes in maintaining the integrity of the organism and in enhancing diversity in the species. As shown here, comparison of the frequencies of intra- and interchromosomal recombination in meiotic and mitotic cells of both mouse and yeast argues that interchromosomal recombination is particularly low in mitotic cells of metazoan organisms. This result in turn suggests that the recombination machinery of metazoa might be organized to avoid the deleterious effects of homozygotization in somatic cells while still deriving the benefits of species diversification and of DNA repair.